Chemistry Teachers’ Level of Scientific Explanation about Change of State and their Beliefs about Scientific Explanation - Emre Harun Karaaslan (Journal of Science Learning, 2022)
The purpose of this study is to examine the capability of chemistry teachers’ scientific explanation on the subject of change of state related to daily life and their beliefs about scientific basis. The sample of this study constituted forty-six chemistry teachers working at different high schools in Gaziantep. The study was conducted following the phenomenographic research method. Within the scope of the study, a test consisting of open-ended questions was conducted to determine the teachers’ capability to make scientific explanations and their beliefs about scientific explanations. Study findings showed that the chemistry teachers participating in this study had inadequacies in making scientific explanations and that their beliefs about scientific explanations were unsatisfactory.